Imaging in electrophysiology - Thornton, Andrew (SA Heart Journal, 2017)
Imaging is becoming increasingly important in clinical cardiac electrophysiology. This article attempts to give a brief overview of what modalities we are presently using, those which may become important, and for what indications we may use them. In addition I will try and convince you why we should use some of them and what data is available concerning some of their potential advantages and drawbacks.